Transition in Turkey: an overview of Bediüzzaman Said Nursi, his life and works for Medresetü’z-Zehra - Kamaruzaman Yusoff; Yilmaz , Omer; Ebrahimi , Mansoureh (Institut Kajian Rantau Asia Barat, 2013)

(untitled)
Bediüzzaman Said Nursi became concerned with reviving Islamic ethics together with traditional Islamic sciences in a highly secularized world. He sacrificed his life for the preservation of Islam in a society dominated by westernization and secularization. Throughout his life, he encountered significant reformations and revolutions in political, educational and social aspects. The present study has twofold objectives. First, it focuses on three different periods of Nursi’s struggles in Turkish society to provide a general view of its eastern and western parts. The impact of Nursi’s political, intellectual and spiritual life had a significant influence on the political and social movements that he established. Second, it discusses about Nursi’s contributions to the revival of Islamic ethics and sciences through of his texts and the Nur movement. To conclude, Nursi’s political movement and struggles in social movements was studied to understand the roots and subsequent growth of the contemporary Nur community and their movement which has spread all over Turkey and different parts of the world. Charisma and leadership attracted the attention of many scholars, politicians and the masses of his time. After his death in 1960, this charisma, reflected in his texts and movement, continued to attract the attention of all levels of society, young and old alike.